Analysis of Coupled Coordination and Driving Factors of Urbanization, Ecosystem Services, and Human Well-Being in the High and Coarse Sediment Yield in the Middle Yellow River - Hong Cao; Qiuchen Zhu; Hua Bai; Hongzhou He; Chunli Liu (Land)
The ecological and social problems brought about by China’s rapid urbanization process threaten sustainable development. Taking the cities with high and coarse sediment yield in the middle reaches of the Yellow River as the research objects, this study constructed a complex analytical framework composed of urbanization, ecosystem service value (ESV), and human well-being (HBW) subsystems. The equivalent factor method (EFM) was used to evaluate the ESV. The entropy weight method (EWM) and the comprehensive nighttime light index (CNLI) were adopted to assess the level of urbanization and human well-being. Then, coupled coordination degree (CCD) and grey relational modes were developed to reveal the level and major obstacles of synergistic development. The results showed that, from 2000 to 2020, urbanization, ESV, and HWB increased. The average value of CCD grew from 0.34 to 0.56, with higher coordination levels in the northeast and south. The coordinated development is influenced by multiple factors, with the intensity of the driving factors decreasing in the order of industrial structure, population quality, economic drive, government regulation, and scientific and technological support. The results indicate that it is essential to formulate differentiated regionally coordinated development strategies and establish cross-regional cooperation mechanisms to achieve interactive urban economic development, ecological protection, and well-being improvements in the middle reaches of the Yellow River.